2020
DOI: 10.1002/bio.3909
|View full text |Cite
|
Sign up to set email alerts
|

A reactive probe for Co2+ ion detection based on a catalytic decomposition process and its fluorescence imaging in living cells

Abstract: A novel reactive fluorescent probe for cobalt ions was prepared based on integration of thiourea functional groups, coumarin, and naphthalimide fluorophores. There was no fluorescence observed for the probe itself, however, in the presence of cobalt ions, catalytic decomposition occurred for the probe and coumarin molecular fragments were produced that emitted blue fluorescence. This enabled the probe to be used as a ‘turn on’ reagent for detection of cobalt ions. Under physiological pH conditions and in appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…He and co-workers prepared 330 , which comprises 1,8-napthimide and 4-aminocoumarin fluorophores linked by a thiosemicarbazide . The probe alone has very weak fluorescence, but undergoes a 87-fold increase in intensity at 425 nm corresponding to the emission wavelength for the coumarin.…”
Section: Fluorescent Sensors For Cobaltmentioning
confidence: 99%
See 1 more Smart Citation
“…He and co-workers prepared 330 , which comprises 1,8-napthimide and 4-aminocoumarin fluorophores linked by a thiosemicarbazide . The probe alone has very weak fluorescence, but undergoes a 87-fold increase in intensity at 425 nm corresponding to the emission wavelength for the coumarin.…”
Section: Fluorescent Sensors For Cobaltmentioning
confidence: 99%
“…He and co-workers prepared 330, which comprises 1,8napthimide and 4-aminocoumarin fluorophores linked by a thiosemicarbazide. 529 The probe alone has very weak fluorescence, but undergoes a 87-fold increase in intensity at 425 nm corresponding to the emission wavelength for the coumarin. Mechanistic studies suggested that Co(II) binding to the thiosemicarbazide results in cleavage of the naphthalimide-N bond, releasing the coumarin thiosemicarbazide, which subsequently decomposes to 4-aminocoumarin.…”
Section: Activity-based Fluorescent Sensors For Co(ii)mentioning
confidence: 99%
“…The main application of probe 36 was the detection of cobalt ions in HeLa cells. 65 Chemosensor 38 based on a coumarin ring was synthesised. An absorption band was observed at 470 nm when this probe was analysed by the ultraviolet-visible spectroscopic technique The pH range of 2.0 to 12.5 was found to be the best working range for probe 38.…”
Section: Ligands For the Detection Of Cobalt Ionsmentioning
confidence: 99%
“…S18 †). And according to the formula Ln[(F max − F t )/ F max ] ¼ −k't, 52,53 their pseudo-rst-order rate constants were determined as 1.49 Â 10 −2 s −1 (Fig. S19a †) and 1.23 Â 10 −2 s −1 (Fig.…”
Section: The Optical Response Of Bs1 and Bs2 Toward Onoo −mentioning
confidence: 99%